PERAN KEPERCAYAAN NASABAH DALAM MEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - Purwa, Ida Bagus Ngurah Satwika; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Manajemen, 2018)
The purpose of this study is to determine the role of customer confidence in mediating the influence of service quality on customer satisfaction. This research was conducted at PT. Satwika Purwa Negara which is an independent marketing office of Prudential Indonesia. Number of customers served in PT. Satwika Purwa Negara reaches 8000 more customers. The number of samples taken is 100 people, using technique of non probability sampling with path as technique of data analysis. Based on the results of the analysis found that the quality of service significantly influence the belief customer at PT. Satwika Purwa Negara, the better the level of service quality, the higher the trust obtained by the customer. Customer confidence has a significant effect on customer satisfaction of PT. Satwika Purwa Negara, the higher the customer's trust, the more easily available customer satisfaction. Quality of service significantly influence customer satisfaction PT. Satwika Purwa Negara, the better the level of service provided then customer satisfaction can be created. Customer confidence is an intervening variable that connects service quality with customer satisfaction at PT. Satwika Purwa Negara.   Keywords: service quality, customer trust, customer satisfaction.